A comparison of the NCT Reichert R7 with Goldmann applanation tonometry and the Reichert ocular response analyzer - Jorge, Jorge (2011)
P>Purpose:The aim of this study was to evaluate the accuracy of intraocular pressure (IOP) values from the new non-contact tonometer (NCT) Reichert R7 by comparing results with those from Goldmann applanation tonometry (GAT) and the Reichert Ocular Response Analyzer (ORA). Other ocular dimensions were assessed to evaluate their potential influence on the IOP values obtained.Methods:Ninety two right eyes from 92 adults aged between 21 and 59 years (mean 34.9 +/- 11.7 years) were enrolled in this study. IOP was measured with R7, ORA and GAT. All measurements were taken between 14:00 and 16:00 in the afternoon. Corneal resistance factor (CRF) and corneal hysteresis were measured with the Reichert ORA. The spherical equivalent refractive error was obtained using an open field auto-refractor (WAM5500; Grand Seiko) and corneal curvature, anterior chamber depth, corneal diameter and axial length were assessed with an optical coherence biometer (IOL Master; Zeiss Meditec, CA, USA).Results:The mean values for IOP measurements were 15.20 +/- 3.37 mmHg (R7), 13.49 +/- 3.55 mmHg (GAT), 15.01 +/- 3.38 mmHg (ORA IOPcc) and 14.44 +/- 3.47 mmHg (ORA IOPg). With the exception of the CRF (rho = 0.72 p < 0.001) the correlations between ocular parameters and IOP obtained with the R7 were neither statistically nor clinically significant.Conclusions:The new NCT, R7 overestimated the IOP compared with GAT in normal, healthy eyes by about 1.7 mmHg on average (95% confidence range of approximately -2 to +6mmHg). The measures provided by the R7 were significantly influenced by the stiffness of the corneal tissue as measured by the ORA CRF value but not by other dimensional parameters of the eye.